The technological challenges of reducing the sugar content of foods. Issue 3 (3rd September 2020) - Erickson, S.; Carr, J.
Abstract: The reduction of sugar and energy (calories) in the diet has been a long‐standing challenge for the food industry, not only to support individuals actively seeking to limit their sugar and energy (calorie) intake but also as a response to public health policy initiatives, such as sugar taxes for the food industry and government reformulation programmes. In recent years, responding to this challenge has become more difficult for food manufacturers and formulators, as consumers are increasingly seeking products formulated using a limited range of natural, clean‐label ingredients. Zero‐calorie high‐potency sweeteners with improved taste performance are a partial solution, but a greater challenge is the replacement of the bulking, browning and other properties that sucrose, glucose and fructose provide in many solid food products. This article describes advances in high‐potency sweeteners and in bulk, low‐calorie sugar replacement ingredients that can offer effective solutions to the challenges encountered in developing great‐tasting, sugar‐ and calorie‐reduced food products for today's consumers.